A micromechanics model for FRC composites. Issue 1 (25th October 2016) - Timothy, Jithender J.; Zhan, Yijian; Meschke, Günther
Abstract: A multiscale model for FRC composite structures taking into consideration the complex interactions at the scales of the fiber and microcracks is proposed. At the scale of the single fiber, a semi‐analytical model characterizes the microslip behavior at the interface between the matrix and the fiber in terms of the overall composite stresses. The influence of fiber bundles on microcrack bridging and arrest is taken into account within the framework of linear elastic fracture mechanics. Upscaling to the macroscopic level using continuum micromechanics shows that the macroscopic deformation of the FRC composite is governed by a 'TERZAGHI' like effective stress. For the finite element analyses of failure behavior at the scale of the composite structure, an 'interface solid element' technique is used to consider localized cracking. Selected numerical and semi‐analytical results together with experimental validations are provided. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)